ANALYSIS OF AGROTOURISM MANAGEMENT, GOVERNMENT POLICIES, AND ENTREPRENEURSHIP ON THE SUSTAINABILITY OF AGROTOURISM IN MALANG REGENCY - Juvitasari, Deana Aulia; Maulidah, Silvana; Riana, Fitria Dina (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Agritourism, as tourism centered around agricultural activities, attracts many travelers with its unique offerings. Malang Regency is a key region for agritourism, with various subdistricts contributing to this sector. However, the advancement of agritourism in Malang Regency is hindered by several significant challenges. The objective of this study is to investigate the sustainability of agriculture-based tourism in Malang Regency by analyzing agritourism management, government policies, and entrepreneurship in relation to the aforementioned issues. The descriptive analytic research approach was employed, with data collected via interviews and literature reviews. The sample size was determined by snowball sampling with 80 managers involved. This study employs descriptive statistical analysis, likert scales, and Structural Equation Modeling-Partial Least Squares (SEM-PLS) utilizing WarpPLS 7.0 software. This study found that agritourism management, government policy, and entrepreneurship all have a beneficial effect and significant impact on the sustainability of agritourism. This is a recommendation in an effort to build sustainable agritourism with active contributions from agritourism managers, effective government policies, and building the entrepreneurial spirit of agritourism managers in Malang Regency.